Descrição e representação de fotografias de cenas e fotogramas de filmes: esquema facetado e em níveis - Cordeiro, Rosa Inês de Novais (1990)
Structure's elaboration of a Indexation Schedule faceted and in levels, aiming the descriptio and representation of information contained in stills and movies photograms. Identification and establishment of criterias for indexation and retrieval of that kind of material. Lay-out of diagram with components that reproduces the identifieds and established criterias at a proposed Diagram on stills and photograms of movies included at the magazine Cahiers du Cinema. The format of the referred Schedule is of easy comprehension and applicability. Itens, categories, facets and sub-facets at the diagram were appropiate to the potencial information of indexed stills and photograms.